Porous titanium for biomedical applications: An experimental study on rabbits - de Vasconcellos, Luana-Marotta-Reis [UNESP] (2010)
Objective: The aim of this study was to carry out an in vivo assessment of bone ingrowth in two different types of porous titanium -the first being completely porous, and the second with a porous surface and dense nucleus, manufactured by powder metallurgy- and to evaluate their mechanical properties. Study design: Ten scaffolds from each group were submitted to metallographic analysis and compression tests. Next, two scaffolds of each type were inserted into 14 rabbits, which were sacrificed 8 weeks after surgery. The samples were submitted for histological examination. Results: Metallographic analysis revealed interconnected pores, and the average interconnected pore diameter was about 360 mm, with 36% total porosity. The totally porous titanium samples and the titanium samples with porous surface and dense nucleus showed an average compressive strength of 16.19 MPa and 69.27 MPa, respectively. After 8 weeks, the animals showed bone ingrowth, even into the most internal pores. Conclusions: The pore morphology was effective in permitting bone ingrowth in both groups. Titanium scaffolds with a porous surface and dense nucleus showed the best mechanical properties and most adequate interface.